Adaptasi dan Validasi Awal Skala BANGS Versi Bahasa Indonesia: Eksplorasi dan Konfirmasi Struktur Dua Faktor melalui EFA dan CFA - Prasetya, Genta; Maharani, Widya; Lusiria, Devi (YASIN, 2025)
This study aims to adapt and conduct an initial validation of the Indonesian version of the Basic Needs in Games Scale (BANGS), a psychometric instrument based on Self-Determination Theory (SDT) that measures two core dimensions in the gaming context: satisfaction and frustration of basic psychological needs. The adaptation process involved forward-backward translation and expert evaluation to ensure cultural relevance. Data were collected from 300 active online game players in Indonesia. Construct validity was assessed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). EFA identified two factors, Need Satisfaction and Need Frustration that accounted for 56.5% of the total variance, with high factor loadings and no cross-loadings. CFA results indicated a good model fit (CFI = 0.951; TLI = 0.944; RMSEA = 0.068; SRMR = 0.055), with all indicators showing significant loadings on their respective factors. These findings confirm that the Indonesian version of the BANGS has adequate psychometric validity and can be reliably used to assess psychological need experiences in gaming activities, while also contributing to cross-cultural research and the development of digital context-based interventions.